Three Perspectives on the Multiplicity of Memory - Hladík, Radim (Teorie vědy / Theory of Science, 2011)
The article affirms that a reasonable number of works have been published recently in Czech language, which should theoretically underpin a wider conception of memory studies. At the same time, these studies should not be subsumed under historiography, and above all, they should not employ solely the concepts of identity and social bonds, but also of power and conflict.